Carrigan Grow: capstone - Grow, Carrigan, artist (Colorado State University. Libraries, 2025)
The artist's statement: How does it look to carry a burden? When does justice start to taste bitter? What does it mean to feel forgiven? Who determines the smell of sweetness? Must I use words to speak? These are some of the questions surrounding Creation that drive my painting practice. I explore these ideas intuitively utilizing a variety of different materials to describe the nuances of the human spirit. Gesture is emphasized before representation to communicate what can be felt and not understood. Though my paintings are rarely premeditated, the human figure, written words, and vibrant colors often find their way into the work. Some ideas manifest quickly onto scraps of paper, others are loosely fleshed out on awkward wooden panels. I am interested in the way my materials operate on varied surfaces. A muted pastel, under a thick oil pastel, scratched into with an unsharpened pencil, work together as instruments in a symphony. My varied layers work to create different levels of intimacy with the paintings and the stories behind them. I do not expect the viewer to gain a direct narrative from the work, but I hope to provoke thoughtful reflection upon Creation and our mysterious place in it.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting